A non-contact vital signs detection method with 77-GHz mmWave FMCW radar - Zhu, Zimao; Wang, XianPeng; Guo, Yuehao; Li, Liangliang (Proceedings of SPIE, the international society for optical engineering, 2025)
Non-contact radar detection technology has become increasingly popular because it provides a more comfortable experience for the human body than contact detection methods. This paper introduces an effective method for vital signs detection using frequency modulated continuous wave (FMCW) radar. Although the accuracy of breathing estimation is typically limited by noise and heart rate estimation is primarily hindered by strong interference from the breathing signal and its higher-order harmonics. A complete ensemble empirical mode decomposition with adaptive noise-subspace pursuit (CEEMDAN-SP) method for respiratory and heartbeat signal reconstruction is proposed to accurately reconstruct the signal by removing noise and interference. The proposed algorithm is validated utilizing a 77G-Hz FMCW radar and compared with a contact device. Experimental results from eight subjects (four males and four females) show that the proposed algorithm effectively enhances estimation accuracy by eliminating noise and interference.